Managing atypical and typical herpetic central nervous system infections: results of a multinational study. (June 2016) - Cag, Y.; Erdem, H.; Leib, S.; Defres, S.; Kaya, S.; Larsen, L.; Poljak, M.; Ozturk-Engin, D.; Barsic, B.; Argemi, X.; Sørensen, S.M.; Bohr, A.L.; et al.
Abstract: There have been many studies pertaining to the management of herpetic meningoencephalitis (HME), but the majority of them have focussed on virologically unconfirmed cases or included only small sample sizes. We have conducted a multicentre study aimed at providing management strategies for HME. Overall, 501 adult patients with PCR-proven HME were included retrospectively from 35 referral centres in 10 countries; 496 patients were found to be eligible for the analysis. Cerebrospinal fluid (CSF) analysis using a PCR assay yielded herpes simplex virus (HSV)-1 DNA in 351 patients (70.8%), HSV-2 DNA in 83 patients (16.7%) and undefined HSV DNA type in 62 patients (12.5%). A total of 379 patients (76.4%) had at least one of the specified characteristics of encephalitis, and we placed these patients into the encephalitis presentation group. The remaining 117 patients (23.6%) had none of these findings, and these patients were placed in the nonencephalitis presentation group. Abnormalities suggestive of encephalitis were detected in magnetic resonance imaging (MRI) in 83.9% of the patients and in electroencephalography (EEG) in 91.0% of patients in the encephalitis presentation group. In the nonencephalitis presentation group, MRI and EEG data were suggestive of encephalitis in 33.3 and 61.9% of patients, respectively. However, the concomitant use of MRI and EEG indicated encephalitis in 96.3 and 87.5% of the cases with and without encephalitic clinical presentation, respectively. Considering the subtle nature of HME, CSF HSV PCR, EEG and MRI data should be collected for all patients with a central nervous system infection.